The Effects of Visual Arts and Animated Film Therapy in Managing Emotional Fatigue in Preschool Children Hospitalized in the Pediatric Ward of RSUD Poso - Supetran, I Wayan; Langitan, Rosamey Elleke; Agusrianto, Agusrianto; Ndama, Metrys; Rantesigi, Nirva (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Preschool-aged children who experience hospitalization in a pediatric ward often face a variety of emotional challenges, including emotional exhaustion. Hospitalization is a frightening and stressful experience for children, especially when they are separated from their family and peers. Visual art and animation film therapy have been recognized as effective therapeutic methods for addressing children's emotional exhaustion and stress. Visual arts play therapy allows children to express their feelings, overcome anxiety, and build emotional connections with their surroundings. The study aimed to look at the effects of visual art play therapy and animated films on managing emotional exhaustion in hospitalized preschool-age children. The data were collected through observation, interviews, and questionnaires given to parents. The result obtained by the treatment group's mean emotional exhaustion score before the action was 32.20, and after the action was 21.80. Wilcoxon statistical analysis, p-value = 0.001. So, it is concluded that there is a significant decrease in children's emotional exhaustion before and after therapy. The conclusion of this study can help improve the care and well-being of preschool children who experience hospitalization, as well as provide valuable insights for health practitioners and educators in supporting the emotional development of children in challenging medical situations.